Ã˜Â¯Ã™Ë†Ã˜Â±Ã˜Â§Ã™â€žÃ™Ë†Ã™â€šÃ™Â Ã™ÂÃ™â€° Ã˜ÂªÃ™â€ Ã™â€¦Ã™Å Ã˜Â© Ã˜Â§Ã™â€žÃ˜ÂªÃ˜Â±Ã˜Â¨Ã™Å Ã˜Â© Ã˜Â§Ã™â€žÃ˜Â¥Ã˜Â³Ã™â€žÃ˜Â§Ã™â€¦Ã™Å Ã˜Â©: Ã˜ÂªÃ˜Â¬Ã˜Â±Ã˜Â¨Ã˜Â© Ã™â€¦Ã˜Â¹Ã™â€¡Ã˜Â¯ Ã˜Â¯Ã˜Â§Ã˜Â± Ã˜Â§Ã™â€žÃ˜Â³Ã™â€žÃ˜Â§Ã™â€¦ Ã™â€žÃ™â€žÃ˜ÂªÃ˜Â±Ã˜Â¨Ã™Å Ã˜Â© Ã˜Â§Ã™â€žÃ˜Â§Ã˜Â³Ã™â€žÃ˜Â§Ã™â€¦Ã™Å Ã˜Â© Ã˜Â§Ã™â€žÃ˜ÂÃ˜Â¯ Ã™Å Ã˜Â«Ã˜Â© Ã˜Â¨Ã™Æ’Ã™Ë†Ã™â€ Ã˜ÂªÃ™Ë†Ã˜Â± Ã™ÂÃ™Ë†Ã™â€ Ã™Ë†Ã˜Â±Ã™Ë†Ã™Æ’Ã™Ë† Ã˜Â§Ã™â€ Ã˜Â¯Ã™Ë†Ã™â€ Ã™Å Ã˜Â³Ã™Å Ã˜Â§ - Ã˜Â²Ã˜Â±Ã™Æ’Ã˜Â´Ã™â€°, Ã˜Â§Ã™â€žÃ˜Â¯Ã™Æ’Ã˜ÂªÃ™Ë†Ã˜Â± Ã˜Â£Ã™â€¦Ã™â€ž Ã™ÂÃ˜ÂªÃ˜Â Ã˜Â§Ã™â€žÃ™â€žÃ™â€¡ (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam UIN Sunan Ampel Surabaya, 2014)
Ã™â€šÃ˜Â¯ Ã™Ë†Ã™â€šÃ˜Â¹Ã˜Âª Ã˜Â§Ã™â€žÃ˜Â£Ã˜Â²Ã™â€¦Ã˜Â§Ã˜Âª Ã˜Â§Ã™â€žÃ˜Â¥Ã™â€šÃ˜ÂªÃ˜ÂµÃ˜Â§Ã˜Â¯Ã™Å Ã˜Â© Ã˜Â§Ã™â€žÃ˜Â´Ã˜Â¯Ã™Å Ã˜Â¯Ã˜Â© Ã™ÂÃ™Å Ã˜Â¨Ã˜Â¹Ã˜Â¶ Ã˜Â§Ã™â€žÃ˜Â¯Ã™Ë†Ã™â€ž Ã˜Â¨Ã™â€šÃ˜Â§Ã˜Â±Ã˜Â§Ã˜Âª Ã˜Â£Ã™Ë†Ã˜Â±Ã˜Â¨Ã˜Â§ Ã™Ë†Ã˜Â£Ã™â€¦Ã˜Â±Ã™Å Ã™Æ’Ã˜Â§ Ã™ÂÃ™Å Ã™â€¡Ã˜Â°Ã™â€¡ Ã˜Â§Ã™â€žÃ˜Â¢Ã™Ë†Ã˜Â§Ã™â€ Ã˜Â§Ã™â€žÃ˜Â£Ã˜Â®Ã™Å Ã˜Â±Ã˜Â©Ã˜Å’ Ã˜ÂªÃ˜ÂÃ˜ÂªÃ˜Â§Ã˜Â¬ Ã˜Â¥Ã™â€žÃ™Å Ã™â€¦Ã˜Â¹Ã˜Â§Ã™â€žÃ˜Â¬Ã˜ÂªÃ™â€¡Ã˜Â§ Ã˜Â¨Ã˜Â´Ã™Æ’Ã™â€ž Ã˜Â¬Ã˜Â¯Ã™Å Ã˜Å’ Ã™â€¦Ã™â€ Ã™â€šÃ˜Â¨Ã™â€ž Ã˜Â£Ã™â€ Ã˜ÂªÃ˜ÂªÃ˜Â£Ã˜Â«Ã˜Â± Ã˜Â¥Ã™â€žÃ™Å Ã˜Â¨Ã™â€šÃ™Å Ã˜Â© Ã˜Â¨Ã˜Â¹Ã˜Â¶ Ã˜Â§Ã™â€žÃ˜Â¯Ã™Ë†Ã™â€ž Ã™ÂÃ™Å Ã˜Â§Ã™â€žÃ˜Â¹Ã˜Â§Ã™â€žÃ™â€¦. Ã™ÂÃ˜Â¨Ã™Ë†Ã˜Â¬Ã™â€¡ Ã˜Â§Ã™â€žÃ˜Â®Ã˜Â§Ã˜Âµ Ã™ÂÃ™â€° Ã˜Â§Ã™â€žÃ˜Â¹Ã˜Â§Ã™â€žÃ™â€¦ Ã˜Â§Ã™â€žÃ˜Â¥Ã˜Â³Ã™â€žÃ˜Â§Ã™â€¦Ã™â€°. Ã™ÂÃ˜Â§Ã™â€žÃ™Å Ã™Ë†Ã™â€¦ Ã˜Â£Ã™â€ Ã˜Â§Ã™â€žÃ™â€¦Ã˜Â³Ã™â€žÃ™â€¦Ã™Å Ã™â€ Ã™â€¦Ã˜Â·Ã˜Â§Ã™â€žÃ˜Â¨Ã™Ë†Ã™â€ Ã˜Â§Ã™â€žÃ˜Â¹Ã™Ë†Ã˜Â¯Ã˜Â© Ã˜Â¥Ã™â€žÃ™â€° Ã™â€ Ã˜Â¸Ã˜Â§Ã™â€¦ Ã˜Â§Ã™â€žÃ™Ë†Ã™â€šÃ™Â Ã˜Â§Ã™â€žÃ˜Â¥Ã˜Â³Ã™â€žÃ˜Â§Ã™â€¦Ã™â€° Ã™Ë†Ã˜Â¥Ã˜ÂÃ™Å Ã˜Â§Ã˜Â¡ Ã™â€¡Ã˜Â°Ã™â€¡ Ã˜Â§Ã™â€žÃ™â€¦Ã˜Â¤Ã˜Â³Ã˜Â³Ã˜Â© Ã˜Â§Ã™â€žÃ™â€¦Ã˜ÂªÃ™â€¦Ã™Å Ã˜Â²Ã˜Â© Ã˜Â§Ã™â€žÃ˜ÂªÃ™â€° Ã™â€šÃ˜Â¯Ã™â€¦Ã˜Âª Ã˜Â§Ã™â€žÃ˜Â®Ã™Å Ã˜Â± Ã˜Â§Ã™â€žÃ™Ë†Ã™ÂÃ™Å Ã˜Â± Ã™â€žÃ™â€žÃ˜Â£Ã™â€¦Ã˜Â©. Ã˜Â¹Ã˜Â±Ã™ÂÃ™â€ Ã˜Â§ Ã˜Â£Ã™â€ Ã˜Â§Ã™â€žÃ™Ë†Ã™â€šÃ™Â Ã™â€¡Ã™Ë† Ã˜ÂÃ˜Â¨Ã˜Â³ Ã˜Â§Ã™â€žÃ™â€¦Ã˜Â§Ã™â€ž Ã˜Â³Ã™Ë†Ã˜Â§Ã˜Â¡ Ã™Æ’Ã˜Â§Ã™â€ Ã˜Â¨Ã˜ÂµÃ™Ë†Ã˜Â±Ã˜Â© Ã˜Â£Ã˜Â¨Ã˜Â¯Ã™Å Ã˜Â© Ã˜Â£Ã™Ë† Ã™â€¦Ã˜Â¤Ã™â€šÃ™â‚¬Ã˜ÂªÃ˜Â©Ã˜Å’ Ã™â€žÃ™Å Ã˜Â³Ã˜ÂªÃ™ÂÃ™Å Ã˜Â¯ Ã™â€¦Ã™â€ Ã™â€¡ Ã˜Â§Ã™â€žÃ™â€ Ã˜Â§Ã˜Â³ Ã™â€¦Ã˜Â¨Ã˜Â§Ã˜Â´Ã˜Â±Ã˜Â© Ã˜Â£Ã™Ë† Ã˜ÂºÃ™Å Ã˜Â± Ã™â€¦Ã˜Â¨Ã˜Â§Ã˜Â´Ã˜Â±Ã˜Â© Ã™Ë† Ã˜Â§Ã˜Â³Ã˜ÂªÃ™ÂÃ˜Â§Ã˜Â¯Ã˜Â© Ã™â€¦Ã™â€ Ã˜Â§Ã™ÂÃ˜Â¹ Ã™â€ Ã˜ÂªÃ™Å Ã˜Â¬Ã˜ÂªÃ™â€¡Ã˜Â§ Ã™â€¦Ã˜ÂªÃ™Æ’Ã˜Â±Ã˜Â±Ã˜Â§ Ã™ÂÃ™â€° Ã˜Â³Ã˜Â¨Ã™Å Ã™â€ž Ã˜Â§Ã™â€žÃ˜Â®Ã™Å Ã˜Â± Ã˜Â§Ã™â€žÃ˜Â¹Ã˜Â§Ã™â€¦ Ã˜Â£Ã™Ë† Ã˜Â§Ã™â€žÃ˜Â®Ã˜Â§Ã˜Âµ. Ã™ÂÃ™â€¡Ã˜Â°Ã˜Â§ Ã˜Â§Ã™â€žÃ˜Â¨Ã˜ÂÃ˜Â« Ã˜Â³Ã™Å Ã˜Â´Ã˜Â±Ã˜Â Ã˜Â´Ã˜Â±Ã˜ÂÃ˜Â§Ã™Ë†Ã˜Â§Ã™ÂÃ™Å Ã˜Â§ Ã˜Â¹Ã™â€ Ã˜ÂÃ™â€šÃ˜Â§Ã˜Â¦Ã™â€š Ã˜Â§Ã™â€žÃ™Ë†Ã™â€šÃ™Â Ã™Ë†Ã˜Â£Ã™â€¡Ã˜Â¯Ã˜Â§Ã™ÂÃ™â€¡ Ã™Ë† Ã˜Â¯Ã™Ë†Ã˜Â±Ã™â€¡ Ã™ÂÃ™â€° Ã˜ÂªÃ™â€ Ã™â€¦Ã™Å Ã˜Â© Ã˜Â§Ã™â€žÃ˜ÂªÃ˜Â±Ã˜Â¨Ã™Å Ã˜Â© Ã˜Â§Ã™â€žÃ˜Â¥Ã˜Â³Ã™â€žÃ˜Â§Ã™â€¦Ã™Å Ã˜Â© : Ã˜ÂªÃ˜Â¬Ã˜Â±Ã˜Â¨Ã˜Â© Ã™â€¦Ã˜Â¹Ã™â€¡Ã˜Â¯ Ã˜Â¯Ã˜Â§Ã˜Â± Ã˜Â§Ã™â€žÃ˜Â³Ã™â€žÃ˜Â§Ã™â€¦ Ã™â€žÃ™â€žÃ˜ÂªÃ˜Â±Ã˜Â¨Ã™Å Ã˜Â© Ã˜Â§Ã™â€žÃ˜Â§Ã˜Â³Ã™â€žÃ˜Â§Ã™â€¦Ã™Å Ã˜Â© Ã˜Â§Ã™â€žÃ˜ÂÃ˜Â¯Ã™Å Ã˜Â«Ã˜Â© Ã˜Â¨Ã™Æ’Ã™Ë†Ã™â€ Ã˜ÂªÃ™Ë†Ã˜Â± Ã™ÂÃ™Ë†Ã™â€ Ã™Ë†Ã˜Â±Ã™Ë†Ã™Æ’Ã™Ë† Ã˜Â§Ã™â€ Ã˜Â¯Ã™Ë†Ã™â€ Ã™Å Ã˜Â³Ã™Å Ã˜Â§. Ã™Ë†Ã™Å Ã˜ÂªÃ™Æ’Ã™Ë†Ã™â€ Ã™â€¡Ã˜Â°Ã˜Â§Ã˜Â§Ã™â€žÃ˜Â¨Ã˜ÂÃ˜Â« Ã™â€¦Ã™â€ : Ã˜ÂªÃ™â€ Ã˜Â¸Ã™Å Ã™â€¦ Ã˜Â£Ã™â€¦Ã™Ë†Ã˜Â§Ã™â€ž Ã˜Â§Ã™â€žÃ™Ë†Ã™â€šÃ™Â Ã™ÂÃ™â€° Ã™â€¦Ã˜Â¹Ã™â€¡Ã˜Â¯ Ã˜Â¯Ã˜Â§Ã˜Â± Ã˜Â§Ã™â€žÃ˜Â³Ã™â€žÃ˜Â§Ã™â€¦ Ã™Æ’Ã™Ë†Ã™â€ Ã˜ÂªÃ™Ë†Ã˜Â± Ã™Ë† Ã˜Â§Ã˜Â¯Ã˜Â§Ã˜Â±Ã˜Â© Ã˜Â§Ã™â€žÃ™Ë†Ã™â€šÃ™Â Ã™ÂÃ™â€° Ã™â€¦Ã˜Â¹Ã™â€¡Ã˜Â¯ Ã˜Â¯Ã˜Â§Ã˜Â± Ã˜Â§Ã™â€žÃ˜Â³Ã™â€žÃ˜Â§Ã™â€¦ Ã™Æ’Ã™Ë†Ã™â€ Ã˜ÂªÃ™Ë†Ã˜Â± Ã™Ë† Ã™ÂÃ™â€žÃ˜Â³Ã™ÂÃ˜Â© Ã˜Â§Ã™â€žÃ˜ÂªÃ˜Â±Ã˜Â¨Ã™Å Ã˜Â© Ã™Ë† Ã™ÂÃ™â€žÃ˜Â³Ã™ÂÃ˜Â© Ã˜Â§Ã™â€žÃ˜ÂÃ™Å Ã˜Â§Ã˜Â© Ã˜Â§Ã™â€žÃ˜ÂªÃ™Å Ã˜ÂªÃ˜Â³Ã™â€¦Ã™â€° Ã™â€¡Ã˜Â°Ã™â€¡ Ã˜Â§Ã™â€žÃ™ÂÃ™â€žÃ˜Â³Ã™ÂÃ˜Â© Ã˜Â¨Ã˜Â±Ã™Ë†Ã˜Â Ã˜Â§Ã™â€žÃ™â€¦Ã˜Â¹Ã™â€¡Ã˜Â¯ Ã˜Â§Ã™â€žÃ˜Â®Ã™â€¦Ã˜Â³ Ã™Ë†Ã™Æ’Ã˜Â°Ã˜Â§Ã™â€žÃ™Æ’ Ã˜Â§Ã™â€žÃ˜Â®Ã˜Â·Ã™Ë†Ã˜Â§Ã˜Âª Ã˜Â§Ã™â€žÃ˜Â®Ã™â€¦Ã˜Â³ Ã™â€žÃ™â€žÃ™â€¦Ã˜Â¹Ã™â€¡Ã˜Â¯ Ã˜Â«Ã™â€¦ Ã˜ÂªÃ™â€ Ã™â€¦Ã™Å Ã˜Â© Ã˜Â£Ã™â€¦Ã™Ë†Ã˜Â§Ã™â€ž Ã˜Â§Ã™â€žÃ™Ë†Ã™â€šÃ™Â Ã™â€žÃ™â€žÃ™â€¦Ã˜ÂµÃ˜Â§Ã™â€žÃ˜Â Ã˜Â§Ã™â€žÃ˜ÂªÃ˜Â±Ã˜Â¨Ã™Ë†Ã™Å Ã˜Â© Ã™ÂÃ™â€° Ã™Æ’Ã™Ë†Ã™â€ Ã˜ÂªÃ™Ë†Ã˜Â±. Ã™Ë†Ã™â€¡Ã™Æ’Ã˜Â°Ã˜Â§ Ã™â€ Ã˜Â³Ã˜Â£Ã™â€ž Ã˜Â§Ã™â€žÃ™â€žÃ™â€¡ Ã˜Â¹Ã˜Â²Ã™Ë†Ã˜Â¬Ã™â€ž Ã˜Â§Ã™â€žÃ™â€¦Ã˜Â³Ã˜ÂªÃ˜Â¹Ã˜Â§Ã™â€ Ã™Ë† Ã˜Â£Ã™â€ Ã™Å Ã˜Â³Ã™â€¡Ã™â€žÃ™â€ Ã˜Â§ Ã™ÂÃ™Å Ã˜ÂªÃ˜Â·Ã˜Â¨Ã™Å Ã™â€š Ã™â€ Ã˜Â¸Ã˜Â±Ã™Å Ã˜Â© Ã˜Â§Ã™â€žÃ™Ë†Ã™â€šÃ™Â Ã˜Â®Ã˜Â§Ã˜ÂµÃ˜Â© Ã™â€žÃ˜Â£Ã˜Â¬Ã™â€ž Ã˜ÂªÃ™â€ Ã™â€¦Ã™Å Ã˜Â© Ã˜Â£Ã™â€¦Ã™Ë†Ã˜Â§Ã™â€ž Ã˜Â§Ã™â€žÃ™Ë†Ã™â€šÃ™Â Ã™â€žÃ™â€žÃ™â€¦Ã˜ÂµÃ˜Â§Ã™â€žÃ˜Â Ã˜Â§Ã™â€žÃ˜ÂªÃ˜Â±Ã˜Â¨Ã™Ë†Ã™Å Ã˜Â© Ã™ÂÃ™â€° Ã™Æ’Ã™Ë†Ã™â€ Ã˜ÂªÃ™Ë†Ã˜Â± Ã™Ë†Ã™â€žÃ™â€žÃ™â€¦Ã˜ÂµÃ˜Â§Ã™â€žÃ˜Â Ã˜Â§Ã™â€žÃ™â€¦Ã˜Â³Ã™â€žÃ™â€¦Ã™Å Ã™â€ Ã™ÂÃ™Å Ã˜Â§Ã™â€žÃ˜Â¹Ã˜Â§Ã™â€žÃ™â€¦ Ã˜Â§Ã™â€žÃ˜Â¥Ã˜Â³Ã™â€žÃ˜Â§Ã™â€¦Ã™Å Ã˜Â¹Ã˜Â§Ã™â€¦Ã˜Â©